Drug discovery for X‐linked adrenoleukodystrophy: An unbiased screen for compounds that lower very long‐chain fatty acids. Issue 10 (30th May 2021) - Moser, Ann B.; Liu, Yanqiu; Shi, Xiaohai; Schrifl, Ulrike; Hiebler, Shandi; Fatemi, Ali; Braverman, Nancy E.; Steinberg, Steven J.; Watkins, Paul A.
Abstract: X‐linked adrenoleukodystrophy (XALD) is a genetic neurologic disorder with multiple phenotypic presentations and limited therapeutic options. The childhood cerebral phenotype (CCALD), a fatal demyelinating disorder affecting about 35% of patients, and the adult‐onset adrenomyeloneuropathy (AMN), a peripheral neuropathy affecting 40%–45% of patients, are both caused by mutations in the ABCD1 gene. Both phenotypes are characterized biochemically by elevated tissue and plasma levels of saturated very long‐chain fatty acids (VLCFA), and an increase in plasma cerotic acid (C26:0), along with the clinical presentation, is diagnostic. Administration of oils containing monounsaturated fatty acids, for example, Lorenzo's oil, lowers patient VLCFA levels and reduced the frequency of development of CCALD in presymptomatic boys. However, this therapy is not currently available. Hematopoietic stem cell transplant and gene therapy remain viable therapies for boys with early progressive cerebral disease. We asked whether any existing approved drugs can lower VLCFA and thus open new therapeutic possibilities for XALD. Using SV40‐transformed and telomerase‐immortalized skin fibroblasts from an XALD patient, we conducted an unbiased screen of a library of approved drugs and natural products for their ability to decrease VLCFA, using measurement of C26:0 in lysophosphatidyl choline (C26‐LPC) by tandem mass spectrometry as the readout. While several candidate drugs were initially identified, further testing in primary fibroblast cell lines from multiple CCALD and AMN patients narrowed the list to one drug, the anti‐hypertensive drug irbesartan. In addition to lowering C26‐LPC, levels of C26:0 and C28:0 in total fibroblast lipids were reduced. The effect of irbesartan was dose dependent between 2 and 10 μM. When male XALD mice received orally administered irbesartan at a dose of 10 mg/kg/day, there was no reduction in plasma C26‐LPC. However, irbesartan failed to lower mouse fibroblast C26‐LPC consistently. The results of these studies indicate a potential therapeutic benefit of irbesartan in XALD that should be validated by further study. Graphical abstract: Lowering cellular levels of saturated very long‐chain fatty acids (VLCFA) has therapeutic benefit in patients with X‐linked adrenoleukodystrophy (XALD). Using immortalized skin fibroblasts from an XALD patient, we conducted an unbiased screen of an approved drug library. We report that the antihypertensiive drug, Irbesartan, consistently lowered VLCFA in primary skin fibroblasts from multiple XALD patients and is worthy of further investigation of its therapeutic potential